2019
DOI: 10.1016/j.jff.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry intake included in hypocaloric diet decreases weight, glucose, cholesterol, triglycerides and adenosine levels in obese subjects

Abstract: Obesity is a disease characterized by an excessive accumulation of fat in the body and it has been linked the enhancement of inflammation-related endogenous molecules, such as adenosine (AD). Since blueberries may induce anti-obesity effects, we tested the hypothesis that blueberries consumption contained in hypocaloric diet would decrease weight, BMI as well as glucose, cholesterol, triglycerides and AD levels in obese subjects. The baseline conditions of obesity-related variables were collected for all subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…On the other hand, Quiang Cheng et al [70] and R. Albuquerque et al [71] studied the extraction of anthocyanins from the fruits of Rubia sylvatica Nakai and from Jabuticaba's epicarp, respectively. Both authors included pH as an influential variable and demonstrated that acid-level pH (3)(4) facilitated the extraction of anthocyanins similarly as it was observed in the present research. Finally, Fibigr et al [72] investigated the optimal amount of açai berry samples for maximum anthocyanin extraction using UAE.…”
Section: Optimal Conditionssupporting
confidence: 76%
See 1 more Smart Citation
“…On the other hand, Quiang Cheng et al [70] and R. Albuquerque et al [71] studied the extraction of anthocyanins from the fruits of Rubia sylvatica Nakai and from Jabuticaba's epicarp, respectively. Both authors included pH as an influential variable and demonstrated that acid-level pH (3)(4) facilitated the extraction of anthocyanins similarly as it was observed in the present research. Finally, Fibigr et al [72] investigated the optimal amount of açai berry samples for maximum anthocyanin extraction using UAE.…”
Section: Optimal Conditionssupporting
confidence: 76%
“…Although blueberry is not so often consumed as fresh fruit, it is increasingly common to find it as the main ingredient in jams and pastry preparations or as a secondary ingredient in different candies or desserts (yogurts, cookies, etc.) [4][5][6]. Moreover, recent investigations have proven its high content in anthocyanins, phenolic compounds, vitamins, and minerals.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were conducted in Asia, 58–60 Europe, 15,44,61–64 the USA, 65–78 South America, 79 Canada 80 and North America, 81 and published between 2010 and 2021. Twenty trials had a parallel study design 44,59,60,63–71,73–78,80,81 and 6 trials had a crossover study design. 15,58,61,62,72,79 The studies used different preparations of blueberry that included blueberry extract, 60,62,63,66,71 freeze-dried blueberry, 15,44,64,65,67,69,70,73–77,80 frozen blueberry, 59,61 blueberry beverages, 58 smoothies, 68 blueberry juice 72 and fruit extract capsules.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the 26 clinical trials conducted on hypertensive, normotensive, MetS, smoker, non-smoker and healthy subjects are summarized in Table 1. These studies were conducted in Asia, [58][59][60] Europe, 15,44,[61][62][63][64] the USA, [65][66][67][68][69][70][71][72][73][74][75][76][77][78] South America, 79 Canada 80 and North America, 81 and pub-lished between 2010 and 2021. Twenty trials had a parallel study design 44,59,60,[63][64][65][66][67][68][69][70][71][73][74][75][76][77][78]80,81 and 6 trials had a crossover study design.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation